Changes in Ochratoxin A concentration during winemaking - Fernandes, Anabela (2007)
The effects of common winemaking procedures on ochratoxin A (OTA) concentrations in the Portuguese wine Vinho Verde were studied. Natural contamination of grapes was not observed, so grapes for vinification were inoculated with Aspergillus carbonarius. Ochratoxin A concentration in these grapes ranged from 0.43 to 7.48 μg/kg. Vinification consistently reduced OTA concentrations in wine independent of the initial OTA concentration in grapes. Mean carry-over of OTA from grapes to wine was 8.1% (w/w) after malolactic fermentation, even without use of enological adjuvants (fining agents). Reduction in OTA was associated with removal of spent fractions during winemaking, such as wine lees after fermentation or sediment after racking. OTA concentrations were higher in these fractions than in the original grapes. Degradation by yeast or bacteria was not observed under the tested conditions.